Creativity in Art, Design and Technology - Liggett, Susan; Earnshaw, Rae.; Townsley, Jill.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This is an open access book. Creativity is a difficult concept, how can it best be defined, understood, applied, and practiced? This book provides important answers to these questions. Technology can enable artists to be more creative. Scientific and artistic thinking give us two complementary tools to understand the complexity of the world, with science reducing subjective experience to essential principles and art intensifying and expanding our experiences. These examples also show how artists can push the boundaries of technology into exciting new realms that have not been explored before. The impact that art and art practice can have on culture, society, and social responsibility is explored in detail through examples and case studies. In addition, the book presents how artists are creating and reflecting cultural and societal resonance in their work. Can other disciplines help artists to be more creative? All are part of an interrelated wider society and enables artists to develop artwork fit for highly interfaced and conceptually broad contemporary contexts. This is illustrated with examples which show exciting and challenging results. Creativity in Art, Design and Technology is relevant for artists, designers, scientists and technologists. All can benefit in a major way from a greater understanding of creativity, and the ways in which mutual interaction and collaboration enables all areas to develop. The potential for the future is immense and this book signposts the way forward.
1 Introduction -- 2 Creativity in the Arts: Traditional and New Media -- 3 Creativity and Artist Technologist -- 4 Creativity and Virtual Worlds -- 5 The Creative Process and Social Responsibility -- 6 Digital Communication as a Creative Tool -- 7 Artificial Intelligence and Creativity -- 8 Art Thinking and Design Thinking -- 9 Time and Temporality: Creative Reception and Repetition -- 10 How can Art assist Science and Technology? -- 11 Research and Development in Creativity -- 12 Epilog.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Design; Application software; User Interfaces and Human Computer Interaction; Design; Computer and Information Systems Applications